Galectin-3 and peripheral artery disease: a Mendelian randomization study - Gou, Yang; Chen, Miao; Zhu, Zhi; Cui, Chi (Frontiers in Cardiovascular Medicine, 2024)
Background Multiple clinical studies have found a significant correlation between elevated galectin-3 (Gal-3) in circulation and the diagnosis and severity of peripheral arterial disease (PAD). The current study used the Mendelian randomization (MR) technique to evaluate the possible causal relationship between Gal-3 and PAD. Methods Genome-wide association study (GWAS) data of Gal-3 and PAD were obtained through the MR-Base platform. Then, using Gal-3 as the exposure and PAD as the outcome, a two-sample MR analysis was performed utilizing several regression techniques, including MR-Egger regression, inverse variance weighted (IVW), weighted median, and weighted mode. Results Six single-nucleotide polymorphisms (SNPs) were identified and designated as instrumental variables (IVs) that exhibited significant correlations with Gal-3 (linkage disequilibrium r2 < 0.001; P < 5 × 10−8). Various statistical methods showed that there was an absence of a significant link between Gal-3 and PAD (IVW: odds ratio (OR) = 0.9869, 95% confidence interval (CI) = 0.8792–1.1078, P = 0.8232). In addition, the presence of genetic pleiotropy did impact the putative causal relationship between PAD and Gal-3 (MR-Egger intercept = 0.0099, P = 0.659). Conclusions There is no current evidence to establish a causal relationship between the level of Gal-3 in circulation and PAD.